Impact of GST on Working Capital Management of SMEs - Dr. N. ThyagaRaju (International Journal of Integrated Research and Practice, 2026)
Goods and Services Tax (GST) in India is an overhaul of the indirect tax system with a vision of creating a single market and tax transparency in India. Although GST has been introduced to ease tax compliance and reduce cascading tax effects, deeper insights are required on the working capital management practices of Small and Medium Enterprises (SMEs) and its impact. This research paper aims to study the impact of the Goods and Services Tax (GST) on the working capital management of SMEs by highlighting the changes in the cash flow position, inventory management, receivables, payables and liquidity position of a SME after the implementation of the GST regime. The effect of GST compliance on the operational efficiency and financial planning of SMEs in various sectors such as input tax credit and online filing of GST returns is explored. A descriptive and analytical research method is used and sources of secondary data are journals, reports, government publications and industry studies. Based on the results, successful implementation of GST has resulted in opportunities and challenges to SMEs. The input tax credit and streamlined taxes have enhanced the efficiency of supply chain and have taken away tax related hassles on one hand. On the other hand, availability of input tax credit and streamlined taxation have helped in streamlining the supply chain efficiency and tax related hassles. Meanwhile, the input tax refund processing has been delayed, compliance obligations have increased and companies have been asked to report digitally every quarter, increasing the burden on the working capital cycles of small businesses that do not have enough capital. The study suggests that the availability of policy support, ease of compliance and timely refund system are essential to remove financial limitations while GST is responsible to create financial discipline and financial transparency among SMEs. The paper provides a valuable input to the policy makers, financial managers and SME owners regarding the potential long term financial impacts of GST on the sustainability of business operations and business performance.